Fracture control in the hangingwall and the interaction between the support system and the overlying strata - Herrmann, Dean Albert. (My University, 2015)
Stress-induced rock fracture is common in deep-level gold mines. Various orientations of fractures result in the formation of unstable blocks of rock which can be a danger and hindrance to mining activities. A study of the effects of an alteration in stope geometry and the influence of two different support systems on the overlying strata was performed. The stresses developed in the rock above an active support load were found to be significantly higher than those predicted by elastic theory. The cutting of a hanging wall dip slot in the back areas of a stope and the allowing of progressive collapse of the strata has been shown to cause large tensile strain changes in the hanging wall and to steepen the dip of extension fractures. Such procedures can be employed to produce competent, stable hanging wall conditions.